The association between the lifestyle risk score and metabolically healthy and unhealthy obesity phenotype in Iranian women with overweight and obesity: a cross-sectional study - Ebrahimi, Sara; Shiraseb, Farideh; Ladaninezhad, Maryam; Izadi, Azimeh; Navaei, Negin; Mirzaei, Khadijeh (Frontiers in Public Health, 2025)
BackgroundThe evidence shows that all women with obesity do not develop metabolic complications thus, they may be metabolically healthy. The lifestyle factors in combination may influence obesity phenotypes including metabolically healthy and unhealthy obesity. While previous studies examined associations between single lifestyle factors and obesity phenotype, no previous study has examined associations between lifestyle risk score (LRS) and obesity phenotypes. This study for the first time created the LRS which is a combination of lifestyle factors and investigated the LRS in relation to various obesity phenotypes among women with overweight and obesity.MethodsThis cross-sectional study analyzed 278 women referred to health centers of the Tehran University of Medical Sciences. A multistage sampling method was used to recruit the participants. The LRS was created based on diet, physical activity (PA), sleep, obesity, and sociodemographic characteristics. A binary logistic regression analysis was used to evaluate the association between obesity phenotypes and LRS.ResultsWomen with higher LRS had higher body mass index (BMI) and high-sensitivity C-reactive protein (hs-CRP) while had lower high-density lipoprotein cholesterol (HDL-C), PA, education levels, sleep quality, vegetables, grains and legumes intake. Furthermore, women with higher LRS were more likely to experience metabolically unhealthy obesity (MUO).ConclusionThis study found significant associations between higher LRS and an increased likelihood of MUO. Further prospective studies are needed to advance our understanding of the relationship between lifestyle and obesity.